Does Elevation Change the Way Current Velocity and Rock Surface Area Affect Benthic Community Composition in an Andean Stream? - Promer, Hunter; Freeburg, Morgan (My University, 2015)
Sampling macroinvertebrates at different altitudes will help determine the importance and interaction of current velocity, substrate surface area and altitude on species abundance and richness.
Color poster with text, photographs, images, and graphs.
Keywords: Andes Mountains; Benthic communities; Macroinvertebrates; Posters